Kepemimpinan Kepala Sekolah dalam Pemberdayaan Manajemen Sekolah - Fedry Saputra (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2022)
Leadership is: "the process of directing and influencing activities related to the work of group members". The leadership approach is divided according to Rivai into 3 approach models, namely the first approach to character, the second approach to behavior, and the third approach to the situation. the goal. The principal has a strategic position in efforts to empower school management. With this strategic position, every principal as an educational leader in schools must have good skills.